2008
DOI: 10.1158/1535-7163.mct-08-0363
|View full text |Cite
|
Sign up to set email alerts
|

Natural polyphenols facilitate elimination of HT-29 colorectal cancer xenografts by chemoradiotherapy: a Bcl-2- and superoxide dismutase 2-dependent mechanism

Abstract: Colorectal cancer is one of the most common malignancies worldwide. The treatment of advanced colorectal cancer with chemotherapy and radiation has two major problems: development of tumor resistance to therapy and nonspecific toxicity towards normal tissues. Different plant-derived polyphenols show anticancer properties and are pharmacologically safe. In vitro growth of human HT-29 colorectal cancer cells is inhibited (f56%) by bioavailable concentrations of trans-pterostilbene (trans-3,5-dimethoxy-4 ¶-hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(63 citation statements)
references
References 61 publications
(58 reference statements)
2
61
0
Order By: Relevance
“…S6A and S6B). To further verify the role of NF-kB signaling in GICs, we used two NF-kB inhibitors, caffeic acid phenethyl ester (CAPE) and pterostilbene (29,30). These inhibitors dramatically blocked the proliferation of both hGIC and NSCL61 in a dosedependent manner (Fig.…”
Section: Eva1 Increased the Expression Of Stemness-related Genes And mentioning
confidence: 99%
“…S6A and S6B). To further verify the role of NF-kB signaling in GICs, we used two NF-kB inhibitors, caffeic acid phenethyl ester (CAPE) and pterostilbene (29,30). These inhibitors dramatically blocked the proliferation of both hGIC and NSCL61 in a dosedependent manner (Fig.…”
Section: Eva1 Increased the Expression Of Stemness-related Genes And mentioning
confidence: 99%
“…Carnosol (43) and carnosic acid (44) are two polyphenols of this group that are of relevance to kinase targeting and they were isolated from culinary herbs that include rosemary, sage and oregano (Table 4) [87].…”
Section: Polyphenolic Diterpenesmentioning
confidence: 99%
“…Several in vitro studies have shown consistent anticancer effects of quercetin in a variety of cancer cell lines and tumors, including U138MG (glioma) [12], HeLa (cervical cancer) [13], MDA-MB-453 (breast cancer) [14], HT-29 (colorectal xenografts) [15], myeloid leukemia [16] and oral cavity cancer [17].…”
Section: Introductionmentioning
confidence: 99%